1995
DOI: 10.1113/jphysiol.1995.sp020585
|View full text |Cite
|
Sign up to set email alerts
|

‘Non‐hypotensive’ hypovolaemia reduces ascending aortic dimensions in humans.

Abstract: 1. The notion that small, 'non-hypotensive' reductions of effective blood volume alter neither arterial pressure nor arterial baroreceptor activity is pervasive in the experimental literature. We tested two hypotheses: (a) that minute arterial pressure and cardiac autonomic outflow changes during hypovolaemia induced by lower body suction in humans are masked by alterations in breathing, and (b) that evidence for arterial baroreflex engagement might be obtained from measurements of thoracic aorta dimensions. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
125
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 32 publications
2
125
3
Order By: Relevance
“…However, straightforward observations of the time course of mean arterial pressure (MAP) following rapid onset of mild LBNP (17, 18) evidenced a transient decrease followed by a recovery of pre-LBNP onset values, suggesting that arterial baroreceptors are affected by mild LBNP as well. More detailed analyses of such transient decreases of MAP in LBNP (13) showed that also systolic blood pressure (SBP) and diastolic blood pressure (DBP) fall and are restored within ϳ15 heart beats, confirming a direct involvement of arterial baroreflex, consistently with previous reports (23,35,45). However, to our knowledge, the quantification of the relative dynamic contribution of arterial and cardiopulmonary baroreflex has not been addressed yet.…”
mentioning
confidence: 50%
“…However, straightforward observations of the time course of mean arterial pressure (MAP) following rapid onset of mild LBNP (17, 18) evidenced a transient decrease followed by a recovery of pre-LBNP onset values, suggesting that arterial baroreceptors are affected by mild LBNP as well. More detailed analyses of such transient decreases of MAP in LBNP (13) showed that also systolic blood pressure (SBP) and diastolic blood pressure (DBP) fall and are restored within ϳ15 heart beats, confirming a direct involvement of arterial baroreflex, consistently with previous reports (23,35,45). However, to our knowledge, the quantification of the relative dynamic contribution of arterial and cardiopulmonary baroreflex has not been addressed yet.…”
mentioning
confidence: 50%
“…During LBNP of 11 mmHg, a level generally ascribed to unload cardiopulmonary receptors (33), although challenged by Taylor et al (46), FVR increased in women but not in men 30 s after the initiation of LBNP (data not shown). Concomitantly, the initial arm capacitance response was greater at LBNP of 11 mmHg in women (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These observations have been interpreted as reflexes triggered by cardiopulmonary baroreceptors (5,12). However, Taylor et al (17) showed that small reductions of effective blood volume reduce aortic baroreceptive areas and trigger hemodynamic adjustments that are so efficient that alterations in AP escape detection by conventional means. In addition, Fu et al (2) reported that arterial baroreceptors are consistently unloaded during low levels (i.e., Ϫ10 and Ϫ15 mmHg) of lower body negative pressure in humans.…”
Section: Discussionmentioning
confidence: 99%